Hyaluronic acid/lactose-modified chitosan electrospun wound dressings - Crosslinking and stability criticalities - Gruppuso, Martina; Iorio, Francesco; Turco, Gianluca; Marsich, Eleonora; Porrelli, Davide (Carbohydrate Polymers, 2022)
Polysaccharide electrospun wound dressings should be an effective strategy in the field of wound care, as they combine an extracellular matrix-like structure with excellent biomimicry. However, their high hydrophilicity and large surface area cause a rapid dissolution in aqueous environments, compromising their clinical employment. In the present paper, electrospun membranes prepared using hyaluronic acid, a bioactive lactose-modified chi-tosan (CTL), and polyethylene oxide have been crosslinked using glutaraldehyde, genipin, EDC/NHS or thermal treatments, obtaining very poor results in terms of membrane stability. Therefore, carbonyldiimidazole (CDI) and methacrylic anhydride were investigated in an innovative way, where CDI proved to be the best compromise between nanofiber water resistance, architecture maintenance and degradability. Indeed, the swelling and degradation behavior as well as the water vapor permeability of these matrices were tested, revealing the effectiveness of the electrospun products in absorbing large amount of liquid while maintaining the balance between water retention and gas permeability.
CRIS-Team WoS Importer:2022-05-27